Host Preference of Epilachna Beetle, Epilachna dodecastigma (Wied.) among Cucurbitaceous Vegetables - Asafuddaullah, M.; Uddin, M.M.; Islam, K.S.; Howlader, M.T.H.; Rahman, M.M. (International Journal of Applied Sciences and Biotechnology, 2015)
A series of experiments were carried out at the field and laboratory of the Department of Entomology, Bangladesh Agricultural University to determine the host preference of Epilachna beetle, Epilachna dodecastigma (Wied.) among four cucurbitaceous crops viz. cucumber, bottle Gourd, sweet Gourd and bitter Gourd. Three varieties of each crop were tested. Data on insect incidence, infestation, food consumption and fecundity of E. dodecastigma were collected. The highest number of Epilachna beetle was recorded on cucumber and the lowest was on bottle Gourd both in open field and in net cage condition. Among the varieties, the highest insect incidence was recorded on Sitol Sosa and the lowest was on BARI Lau-4 both in open field and in net cage. The highest leaf and twig infestation was found on cucumber crop and its’ Sitol Sosa variety, while the lowest was on bottle Gourd crop and its' BARI Lau-4 variety in both open field and in net cage. The Epilachna beetle showed the similar host preference in case of daily food consumption and oviposition rate both in net cage and laboratory condition. Thus, considering the insect incidence, infestation, food consumption and fecundity, the crop cucumber and the tested Sitol Sosa variety appeared to be the most preferred host for Epilachna beetle. Int J Appl Sci Biotechnol, Vol 3(2): 352-358 DOI: http://dx.doi.org/10.3126/ijasbt.v3i2.12809